Rereading the narrated evidences of celibacy from the perspective of Ayatollah Javadi Amoli - ali ghadrdan gharamaleki (حکمت اسرا, 2020)
One of the most important and challenging issues is the knowledge of wisdom, quality and the existence of the soul. Most rational theologians and theologians defend the abstraction of the soul by relying on rational and narrative arguments, while most theologians of the narrative and sectarian school emphasize the physicality of the soul by emphasizing the narrative arguments. Given this contrast, especially in the narrated arguments, the author decided to evaluate the narrated arguments of the issue independently in order to clarify the philosophers' claim that the reason for the abstraction of the soul is not limited to the rational arguments and the support and implication of the narrated arguments on Is celibacy correct or not? Therefore, the purpose of this research is, firstly, to explain the narrated evidences of selflessness in a coherent and independent way in the form of a research, and secondly, to evaluate these evidences whether they imply selflessness or not? For this purpose, Ayatollah Javadi Amoli, a contemporary scholar and commentator, has been discussed. By researching the libraries of narrated evidences that indicate the celibacy of the soul from the point of view of Ayatollah Javadi Amoli, the author has extracted and analyzed them. In this article, it will be clear that most of the narrated evidences of the sages, especially Ayatollah Javadi Amoli, indicate the abstraction of the soul.